2020
DOI: 10.1152/ajprenal.00064.2020
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of DJ-1 in endotoxin-induced acute kidney injury

Abstract: Acute Kidney Injury (AKI) is a frequent complication of sepsis and an important cause of morbidity and mortality worldwide. A cornerstone of sepsis-associated acute kidney injury (SA-AKI) is dysregulated inflammation leading to increased tissue oxidative stress and free radical formation which leads to multiple forms of cell death. DJ-1 is a peroxiredoxin protein with multiple functions including its ability to control cellular oxidative stress. Although DJ-1 is expressed prominently by renal tubules, its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Study have reported that patients with higher serum S100A9 expression tended to suffer from more severe sepsis-related organ dysfunction [ 36 ]. Leeds et al observed that expression of S100A9 was drastically increased in iMCD3 (inner medullary collecting duct cell line) cells from sepsis-induced AKI model exposed to lipopolysaccharide (LPS) serum compared to control group exposed to phosphate-buffered saline (PBS) serum [ 37 ]. The studies suggested S100A9 could be potential diagnostic biomarker of sepsis-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Study have reported that patients with higher serum S100A9 expression tended to suffer from more severe sepsis-related organ dysfunction [ 36 ]. Leeds et al observed that expression of S100A9 was drastically increased in iMCD3 (inner medullary collecting duct cell line) cells from sepsis-induced AKI model exposed to lipopolysaccharide (LPS) serum compared to control group exposed to phosphate-buffered saline (PBS) serum [ 37 ]. The studies suggested S100A9 could be potential diagnostic biomarker of sepsis-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a role of PARK7 in the development of kidney diseases. For instance, Leeds et al demonstrated that activation of PARK7 was renoprotective in lipopolysaccharides-or cecal ligation and puncture-induced septic AKI in mice (34). Shen et al showed that increased expression of renal tubular PARK7 might represent a renoprotective response in a rat model of high glucose-induced diabetic kidney diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to control animals, altered PARK7 levels in kidney tissues have also demonstrated in experimental animal of kidney diseases. An increase of PARK7 levels in kidney tissues was detected in in mouse models of septic AKI, and a ischemiareperfusion-induced rat model in diabetic kidney injury (34,41). Eltoweissy et al showed a disease grade dependent increase of PARK7 levels in the kidneys of a mouse model of COL4A3deficiency-induced renal fibrosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in LPS-induced TNFα and TNFR1 directly damages the glomerular endothelial cell fenestrae and the glomerular endothelial surface layer [8]. We have shown that not only does LPS-induce AKI in mice, but the serum of mice injected with LPS also contains cytotoxic milieu that can directly cause renal epithelial cell death [51,52]. Overall, these studies suggest that LPS-induced AKI can be an effect of direct activity of LPS on renal parenchyma and in parallel the SIRS like condition can result in cytokine driven renal parenchymal damage to collectively worsen outcomes.…”
Section: Key Notesmentioning
confidence: 96%